Analysis of risk factors for postoperative gastrointestinal dysfunction in colorectal cancer patients and construction of a predictive model - Sun Qian; Liu Bei; Zhu Huayuan (结直肠肛门外科)
[Objectives] To analyze the risk factors for postoperative gastrointestinal dysfunction in patients with colorectal cancer and to construct a nomogram predictive model based on these factors. [Methods] A retrospective analysis was conducted on the clinical data of 414 patients who underwent colorectal cancer surgery at The Second People’s Hospital of Huai’an from January 2020 to June 2024. The patients were randomly divided into a modeling group and a validation group in a 7∶3 ratio. The modeling group was further divided into an occurrence group and a non-occurrence group based on the occurrence of postoperative gastrointestinal dysfunction. Baseline and clinical data were collected to screen for risk factors for postoperative gastrointestinal dysfunction in colorectal cancer patients. A nomogram model was constructed based on the identified risk factors to predict postoperative gastrointestinal dysfunction in colorectal cancer patients. The ROC curve was used to analyze the predictive value of the model in both the modeling and validation groups, and the Hosmer-Lemeshow goodness-of-fit test was used to assess the fit of the nomogram model. [Results] There were no statistically significant differences in clinical data between the modeling group and the validation group (P>0.05). Univariate analysis showed that the proportions of patients with age ≥ 60 years, smoking history, BMI > 25 kg/m2, stage Ⅲ-Ⅳcolorectal cancer, low rectal cancer, abdominal fluid accumulation, high ligation of the inferior mesenteric artery, preoperative nutritional score > 4 points, preoperative albumin level ≤ 35 g/L, no fluid therapy after surgery, and no multimodal analgesia after surgery were higher in the occurrence group than in the non-occurrence group (P<0.05). Multivariate Logistic regression analysis revealed that BMI > 25 kg/m2, low rectal cancer, preoperative albumin level ≤ 35 g/L, no fluid therapy after surgery, and no multimodal analgesia after surgery were risk factors for postoperative gastrointestinal dysfunction in colorectal cancer patients (P<0.05). The ROC curve of the nomogram model for predicting postoperative gastrointestinal dysfunction in the modeling group had an AUC of 0.825 (95%CI: 0.775-0.876), and the ROC curve for the validation group had an AUC of 0.818 (95%CI: 0.735-0.901). [Conclusion] BMI > 25 kg/m2, low rectal cancer, preoperative albumin level ≤ 35 g/L, no fluid therapy after surgery, and no multimodal analgesia after surgery are risk factors for postoperative gastrointestinal dysfunction in colorectal cancer patients. The constructed nomogram predictive model demonstrates good accuracy, discrimination, and consistency.